Решить систему уравнения

4×(y-x)-7=x+7y
6-3×(x+y)=5y-2x​​

olga195888 olga195888    1   30.05.2021 22:14    2

Ответы
Алёна542133 Алёна542133  29.06.2021 23:16

Пошаговое объяснение:

4(y-x)-7=x+7y

6-3(x+y)=5y-2x

4y-4x-7=x+7y

6-3x-3y=5y-2x

-3y-5x=7

-x-8y= - 6

-3y-5x=7

X+8y=6 x=6-8y

-3y-5(6-8y)=7

-3y-30+40y=7

37y=7+30

37y=37

y=1

X=6-8×1

X=6-8

X= - 2

ответ : ( - 2;1)

ПОКАЗАТЬ ОТВЕТЫ
Милкаi Милкаi  29.06.2021 23:16

Пошаговое объяснение:

Сначала раскроем скобки:

4у - 4х - 7 = х + 7у

6 - 3х - 3у = 5у - 2х

4у - 4х - х - 7у = 7

-3х - 3у - 5у + 2х = -6

-3у - 5х = 7

-х - 8у = -6

-3у - 5х = 7

х + 8у = 6

-3у - 5х = 7

х = 6 - 8у

1)

-3у - 5х = 7

-3у - 5(6 - 8у) = 7

-3у - 30 + 40у = 7

-3у + 40у = 7 + 30

37у = 37

у = 37 : 37

у = 1

2)

х = 6 - 8у

х = 6 - 8 * 1

х = 6 - 8

х = -2

ответ: (-2; 1)

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика